PERKAWINAN PAKSA DALAM MASYARAKAT BONE DALAM PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF - fahlevi, Andi Fairuz Elisya; Ridwan, Saleh; Ishak, Nurfaika (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2026)
This study aims to analyze the practice of forced marriage in the community of Lamakkaraseng Village, Bone Regency, and to examine its compatibility with Islamic law and Indonesian positive law. This research employs a qualitative approach with a field research design, using observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that both Islamic law and positive law firmly reject the practice of forced marriage, as it contradicts the fundamental principle of consent between the prospective bride and groom. In Islamic law, consent constitutes an essential requirement for the validity of a marriage contract, while in positive law, it is regulated under Law Number 1 of 1974 and Law Number 12 of 2022 on Sexual Violence Crimes, which categorizes forced marriage as a criminal offense. The main contributing factors to this practice include parental dominance, economic pressure, as well as cultural and social legitimization. The impacts are not only social and legal but also psychological, particularly for women as victims. Therefore, strengthening public legal awareness and enhancing the protection of individual rights in choosing a life partner freely are crucial.